Translating aspect: a case study - Stanojević, Mateusz-Milan (Array, 2004)
The paper discusses the notion of aspect and some consequences that the perfective/imperfective distinction may have for translational equivalence. All the relevant terms are defined from a cognitive point of view. Specifically, the paper looks at the verbs of seeing widzieć (imperfective ‘ see’ ) and zobaczyć (perfective ‘ see’ ) in Polish and gives examples of their translation into Croatian using the dual aspect verb vidjeti ‘ see’ . In certain contexts the aspect of the Polish original with all its relevant repercussions for construal can be adequately portrayed in Croatian. In some contexts, however, the Croatian translation is underspecified with respect to the aspect of the original. These contexts are further explored, giving yet another confirmation of the dynamic nature of equivalence.